Penerapan Artificial Intelligence Untuk Chatbot Informasi Mata Pelajaran SMK Informatika Komputer Ampana Kota - Anisa Yulandari; Sri Khaerawati Nur; Sukardi; Anwar Panyili (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Ampana City Computer Informatics Vocational School students have problems with enthusiasm for learning at school due to the lack of motivation provided. As a result, many students are lazy to listen or follow class subjects. From the description of the existing problem, the researcher tried to create information media to provide motivation to students which is related to the benefits and goals of learning, using Artificial Intelligence which is formed in a subject information chatbot. The Naïve Bayes Classifier method is used to build chatbots. Assuming independence between features, Naive Bayes is able to work well on text-based classification such as processing questions and answers in chatbots. So you can answer students' questions accurately. The research results show that the use of chatbots contributes significantly to increasing learning motivation, as shown by the Paired Sample T-test of 0.05, indicating that there is a significant increase in student interest in learning. In addition, system testing shows an accuracy rate of 100% in providing responses to student questions. Artificial intelligence-based chatbots can be an effective innovation in supporting learning and increasing students' interest in learning in technology-based educational institutions.